THE MULTI-LAYERED IDENTITY OF A CITY: ARTICULATING CITIZENS’ AND PLACE IDENTITIES IN YOGYAKARTA AS THE CITY OF PHILOSOPHY - Johannes Parlindungan Siregar (Diponegoro University, 2019)
Identity demonstrates the intrinsic values of a subject or object that can be used to recognise a territory. Through this study, the city of Yogyakarta expresses a complexity of identity making through the implementation of heritage conservation. In practice, the creation of city identity represents government’s effort to promote the city on behalf of local economic development. This paper aims to explaining how the identity connects with the constructed identity in local society. In this sense, the residents or local community contribute to the construction of tradition that is in the central of tourism promotion. The investigation uses one cycle coding analysis to investigate governmental document associated with cultural heritage and placemaking, and interview transcripts. As the result, this paper demonstrates that the identity of Yogyakarta has three layers, i.e. city identity, place identity and citizen’s identity. The three identities express an association between the implementation of heritage conservation policy and the constructed heritage meaning in local society. This article bridges heritage conservation and placemaking, and the creation of identity.